A LEAP Forward in Wildlife Conservation: A Standardized Framework to Determine Mortality Causes in Large GPS‐Tagged Birds - Connor T. Panter; Carina Nebel; Maximilian Raab; Verena Strauss; Clara Freytag; Manuel Wojta; Hannah Böing; Patrick Hacker; Rainhard Raab; Jendrik Windt; Annika Posautz; Anna Kuebber‐Heiss; et al. (Ecology and Evolution)
ABSTRACT Anthropogenic activities threaten many wildlife populations by increasing mortality rates, making it crucial to identify the locations and causes of mortality to inform conservation actions. Technological advancements, such as GPS satellite tracking, enable precise recording of wildlife movements. High‐resolution data from such devices can facilitate rapid carcass recovery and provide insights into the mortality causes of tagged individuals. Obtaining required information to determine these causes is complex, and standardized approaches can overcome these limitations. In this study, we introduce the LIFE EUROKITE Assessment Protocol (LEAP), a framework for determining the timing, locations, and causes of mortality in GPS‐tagged birds. LEAP is a multifaceted approach that integrates: (1) GPS tracking data, (2) evidence from the mortality location (site investigation), and (3) necropsy results to derive the mortality cause and a corresponding certainty score. We supplement the detailed description of LEAP with case studies assessing its effectiveness. Using 329 deceased GPS‐tagged red kites (Milvus milvus) we compared conditions of the carcasses processed using LEAP with 145 opportunistically collected raptor carcasses. We also show that LEAP improves carcass condition and therefore allows for higher quality necropsy results. Additionally, we assessed how availability among sources of information (tracking, site investigation and necropsy) influences the quality of mortality assessments. Applying LEAP with all data sources provided the highest quality assessments in 64% of cases. Some 35% of cases were of high quality without necropsy, instead drawing evidence only from tracking data and site investigations. Predation related mortality was less prevalent (11%) when relying on necropsy compared to cases without necropsy (36%), while poisoning showed the opposite trend. Furthermore, we provide guidelines and empirical examples of mortality assessments. Our standardized LEAP approach ensures the best use of all available information regarding mortality events in GPS‐tagged birds and advances wildlife mortality research as a valuable tool for conservationists and wildlife managers.